2020
DOI: 10.21203/rs.3.rs-15734/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with 2019 Coronavirus disease in a non-Wuhan area of Hubei Province, China: a retrospective study

Abstract: Background: Since December, 2019, the 2019 Coronavirus disease (COVID-19) from Wuhan, China, has caused worldwide outbreak with more than 200,000 people infected and thousands of deaths. The clinical characteristics of COVID-19 patients in non-Wuhan areas of Hubei province have not been described. Methods: We retrospectively analyzed the clinical characteristics and treatment progress of 91 patients diagnosed with COVID-19 in Jingzhou Central Hospital. Results: Of the 91 patients diagnosed with COVID-19, 30 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 6 publications
(10 reference statements)
2
54
0
1
Order By: Relevance
“…Researchers demonstrated that compared with survivors, nonsurvivors were more likely to develop sepsis and multiple organ injuries including acute cardiac injury, ARDS requiring mechanical ventilation, and acute kidney injury requiring dialysis. (Deng, Hu, et al, 2020; Inciardi et al., 2020; Shi, Qin, et al, 2020; Wang, Lu, et al, 2020; Yang et al., 2020a; Zhao, Xu, et al, 2020). Secondary infections (30%) and septic shock (32%) are common among severe COVID‐19 patients (Javanian et al., 2020; Tang et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers demonstrated that compared with survivors, nonsurvivors were more likely to develop sepsis and multiple organ injuries including acute cardiac injury, ARDS requiring mechanical ventilation, and acute kidney injury requiring dialysis. (Deng, Hu, et al, 2020; Inciardi et al., 2020; Shi, Qin, et al, 2020; Wang, Lu, et al, 2020; Yang et al., 2020a; Zhao, Xu, et al, 2020). Secondary infections (30%) and septic shock (32%) are common among severe COVID‐19 patients (Javanian et al., 2020; Tang et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…We performed a meta-analyses using the "meta" package in R software version 3.6.3 (the R Foundation for Statistical Computing, Vienna, Austria). The pooled incidence of AKI in all reported COVID-19 patients from these 26 studies was 6.5% (95% CI 4.1-10.2), with a much higher rate in patients from the ICU (32.5%, 95% CI 21.2-46.3) 8,14,19 than in patients from mixed departments (5.1%, 95% 6,[10][11][12][13][15][16][17][18][20][21][22][23][24][25][26][27][28] (Figure 1a). Studies from Wuhan showed a higher AKI incidence (9.7%, 95% CI 6.2-14.9) than studies from outside Wuhan (2.8%, 95% CI 1.2-6.6%) (Figure 1b).…”
Section: Epidemiology Of Covid-19-associated Acute Kidney Injurymentioning
confidence: 99%
“…This study was supported by grants from the National Natural Science Foundation of The median time was 5 (3, 11) days for admission (n=555), 13 (8,17) for critical illness (n=75), 18 (14,22) for in-hospital AKI (n=21), and 29 (22,38) for death (n=27). Data was presented with median value with 25-75% percentiles.…”
Section: Funding Sourcesmentioning
confidence: 99%
“…Immunological dysfunction due to COVID-19 can potentially result in the derangement of haematological, hepatic and renal laboratory markers. 18,28,31,39,[41][42][43]46,47,50,52,53,57,61,63,64,[69][70][71][72][73] The immunopathogenesis of SARS-CoV-2 infection is typified by an aggressive inflammatory response, 74 and accordingly, elevated inflammatory markers are common. 18,28,[41][42][43]46,47,50,52,61,63,64,[69][70][71][72] Lymphopaenia and an increased neutrophil to lymphocyte ratio can occur in many patients with SARS-CoV-2 infection.…”
Section: Symptoms Associated With Covid-19mentioning
confidence: 99%